Boosting natural history research via metagenomic clean-up of crowdsourced feces - Srivathsan, Amrita (PLoS Biol, 2019)
Biodiversity is in crisis due to habitat destruction and climate change. The conservation of many noncharismatic species is hampered by the lack of data. Yet, natural history research—a major source of information on noncharismatic species—is in decline. We here suggest a remedy for many mammal species, i.e., metagenomic clean-up of fecal samples that are “crowdsourced” during routine field surveys. Based on literature data, we estimate that this approach could yield natural history information for circa 1,000 species within a decade. Metagenomic analysis would simultaneously yield natural history data on diet and gut parasites while enhancing our understanding of host genetics, gut microbiome, and the functional interactions between traditional and new natural history data. We document the power of this approach by carrying out a “metagenomic clean-up” on fecal samples collected during a single night of small mammal trapping in one of Alfred Wallace’s favorite collecting sites.